INVESTIGATING GENDER VIOLENCE IN LATIN AMERICA AND THE CARIBBEAN: A SMALL LITERATURE REVIEW (2017-2019) - Souza Monteiro, Solange Aparecida de [UNESP]; Silva, Claudionor Renato da; Marcal Ribeiro, Paulo Rennes [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
Gender violence assumes an important space for the production of knowledge for the area of Sexual Education, especially when we insert these studies in educational contexts that focus on a curriculum for the school of basic education and higher education, for actions in social spaces such as collectives social movements, political parties and women's empowerment fronts, spaces that can develop fights against feminicide and the various violence suffered by women and other non-male gender groups. The situation of gender violence is aggravated in our current pandemic state brought about by the new Corona Virus, which forcing society to social isolation, made couples and families spend many more moments together, a triggering factor for the increase in violence against women. These changes in the families' way of life reveal the importance of studies in the area of Sexual Education about this subject. We therefore chose to survey the studies published in the last three years and publicized on Google Scholar, whose description and analysis would provide elements that could trigger a discussion on gender violence in Latin America and the Caribbean between researchers and professionals who work with Sexual Education. Building a direction of research on the theme in the field of Sexual Education from the trends of studies of the last three years. We found that there are few published studies, specifically on the Caribbean, an aspect that suggests the need to expand the investigative space and invest in research on gender violence.
Keywords: Gender violence; Sexual education; Latin america; The caribbean